A EVOLUÇÃO DA CIDADANIA FEMININA NO UNIVERSO JURÍDICO: DA INCAPACIDADE RELATIVA À LEI MARIA DA PENHA - Menegon, Carolina; Fabrim, Deisi; Cardoso, Angela T. R.; Gatto, Joaquim H.; Hauser, Ester E.; Grossmann, Lurdes A. (Salão do Conhecimento, 2013)
Resumo